2004
DOI: 10.3141/1892-18
|View full text |Cite
|
Sign up to set email alerts
|

Complementary Application of Radar, Impact-Echo, and Ultrasonics for Testing Concrete Structures and Metallic Tendon Ducts

Abstract: Nondestructive testing of concrete structures plays an increasing role in civil engineering, although until now the full potential of such techniques has not been tapped. For posttensioned structures, the investigation of tendon ducts is one of the most essential testing problems. The location of tendon ducts, the determination of concrete cover and, especially, the detection and quantification of ungrouted areas inside the ducts are the relevant questions. Recent developments and opportunities of radar, impac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…The main advantages of LIBS are the high repetition rate (10 measurements per second) and no need for surface preparation. Results of automated ultrasonic measurement and their fusion with radar data are presented elsewhere (6,9,10). The encouraging results demonstrate the quality and performance in data acquisition and data processing through the procedure described.…”
Section: Laser-induced Breakdown Spectroscopymentioning
confidence: 90%
“…The main advantages of LIBS are the high repetition rate (10 measurements per second) and no need for surface preparation. Results of automated ultrasonic measurement and their fusion with radar data are presented elsewhere (6,9,10). The encouraging results demonstrate the quality and performance in data acquisition and data processing through the procedure described.…”
Section: Laser-induced Breakdown Spectroscopymentioning
confidence: 90%
“…Such an attempt was made by Maierhofer et al [48] who employed the impulse response method and the impact-echo method to assess the safety of use of large-size floors. Also Oh et al [49], who similarly as Maierhofer et al [48], studied the problems relating to the assessment of the safety of use of reinforced concrete structures, including concrete floors, came up with an idea of the combined use of the above methods.…”
Section: Literature Surveymentioning
confidence: 99%
“…Studies have shown GPR is highly effective when combined with other NDT methods (Kohl et al 2005, Maierhofer et al 2004, Cruz et al 2010. The high-speed nature of GPR and its sensitivity to changes in surface dielectric makes it an ideal candidate to use with laser scanning.…”
Section: Ground Penetrating Radarmentioning
confidence: 99%